Research on stem cells: new challenge for Europe. - Altavilla, Annagrazia; Dell'Erba, Alessandro (Medicina e Morale, 2004)
Stem cell research is one of the promising areas of biotechnology, which offers the prospect of developing new methods to repair or replace tissues or cells damaged by injuries or diseases and to treat some serious chronic diseases. Stem cell research is expected to be equally important for basic science to understand cell differentiation and growth. One of the possible sources for stem cells is human pre-implantation embryos. However, when this research involves the use of human embryos, it raises the question of ethical values at stake and of the limits and conditions for such a research. European Union (EU) member states have taken very different positions regarding the regulations of embryonic stem cells research. According to the different ethical, philosophical and religious traditions in which the states are rooted, it confirms that different views exist throughout EU concerning what is and what is not ethically defensible. This article aims to examine the legislations and ethical positions existing on this subject in Europe, as well as the further guidelines on principles for deciding on the Community funding (in the Sixth European Framework Programme for research- FP6) of research projects, involving the use of human embryos and embryonic stem cells. Furthermore, this study is meant to provide starting points of reflexion on the new european integration goals in the biomedical research sector.